The gendered impacts of index-insurance on food-consumption: Evidence from southern Ethiopia - Timu, Anne G.; Gustafson, Christopher R.; Mieno, Taro (Elsevier, 2023)
Index insurance has been promoted as an innovative strategy for enhancing long-term resilience to climate-related shocks and providing financial inclusion, particularly to poor women farmers in developing countries. In this paper, we evaluate the gendered impact of an index-based livestock insurance product on food consumption among pastoral households in southern Ethiopia. We exploit intertemporal variation in household risk exposure and insurance payouts to evaluate the ex ante and ex post insurance impacts and use randomly distributed discount coupons to instrument the insurance purchase variables. We find that during the pre-drought period, a previous season insurance purchase and the intensity of insurance coverage significantly and equally reduces food expenditure in male- and female-headed households. In the post-drought period, we find that an insurance payout significantly increases food expenditure per adult equivalent among female-headed households.